Detection of multiply charged protein ions using matrix-assisted laser desorption/ionization mass spectrometry and a force-dried droplet method with a 2-nitrophloroglucinol matrix. Issue 3 (19th January 2022) - Yun, Kangseok; Jalaludin, Iqbal; Jung, Shinhee; Jang, Kyoung-Soon; Kim, Jeongkwon
Abstract : MALDI-MS of myoglobin using 2-NPG with HCl additive. Abstract : Conventional dried droplet (DD) methods show poor reproducibility in matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) due to the frequent induction of a heterogeneous sample distribution. Recently, a forced dried droplet (FDD) sample preparation method was introduced to form homogeneous samples; this method improves the reproducibility of MALDI-MS analysis and generates highly multiply charged ions compared to DD methods. The FDD method utilizes secondary nucleation to generate a homogeneous sample distribution by applying an external force such as fluid shear stress by stirring the sample using a micropipette tip. In this study, a 2-nitrophloroglucinol (2-NPG) matrix was used for the DD and FDD sample preparation methods, and the charge state and homogeneity were compared by detecting multiply charged ions of proteins including cytochrome c, myoglobin, and immunoglobulin G (IgG) and measuring the relative standard deviation (RSD). FDD with a 2-NPG matrix produced a more homogeneous sample distribution and higher charge state ions than the DD method. FDD with a 2-NPG matrix was applied in MALDI-MS analysis of IgG fragments obtained from sequential reduction of IgG. In addition, FDD with intentional scratching of the MALDI plate by rotating a micropipette tip was found to provide similar or better reproducibility, higher charge state ions, and more uniformly distributed sample morphology compared to FDD without scratching.